“Jus’ hol’ yuh breath an’ kick”: Queer Self-Made Womanhood in Nicole Dennis-Benn’s “Swimmer” ([Inter]sections, 2025)
This article performs a close reading of the essay “Swimmer,” written by the Jamaican American novelist Nicole Dennis-Benn and published in the anthology The Good Immigrant USA: 26 Writers Reflect on America (2019). On the one hand, “Swimmer” endorses the myths of the self-made man and the American dream by describing the remarkable achievements of its author, regardless of all the obstacles in her way. On the other hand, though, it questions the American success mythology by shedding light on the hardships faced by migrants. As a result, this article considers the following research questions: “Does Nicole Dennis-Benn’s ‘Swimmer’ both legitimize and challenge the myth of the self-made man and, by extension, the myth of the American dream?” and, if so, “In which way are the myths of the self-made man and of the American dream simultaneously celebrated and questioned in ‘Swimmer’?”. To do so, this analysis adopts an approach located within the field of cultural studies, embracing its interdisciplinary nature and combining literary studies with American and Jamaican history and culture, while departing from Heike Paul’s problematization of American myths in The Myths that Made America: An Introduction to American Studies (2014).